Novel roles for genetically modified plants in environmental protection - Macek, Tomas; Kotrba, Pavel; Svatos, Ales; Novakova, Martina; Demnerova, Katerina; Mackova, Martina (Trends in biotechnology, 2008)
Transgenic plants of environmental benefit typically consist of plants that either reduce the input of agrochemicals into the environment or make the biological remediation of contaminated areas more efficient. Examples include the construction of species that result in reduced pesticide use and of species that contain genes for either the degradation of organics or the increased accumulation of inorganics. Cutting-edge approaches, illustrated by our own work, focus on the applicability of genetically modified (GM) plants that produce insect pheromones or that are specifically tailored to the phytoremediation of cadmium or PCBs. This paper discusses the role that the next generation of GM plants might play in preventing and reducing chemical contamination and in converting contaminated sites into safe agricultural or recreational land.
Keywords: znečištění životního prostředí; Environmental Pollutants; Biodegradation, Environmental; biodegradace; látky znečišťující životní prostředí; Environmental Pollution; zachování přírodních zdrojů; geneticky modifikované rostliny; Plants, Genetically Modified; Conservation of Natural Resources